TLC–Densitometry for Determination of Omeprazole in Simple and Combined Pharmaceutical Preparations - Wioletta Parys; Alina Pyka-Pająk (Pharmaceuticals, 2022)
TLC combined with densitometry was used and chromatographic conditions developed to separate omeprazole and diclofenac sodium from their potential impurities. The development of the TLC–densitometry method is based on the elaboration of new chromatographic conditions allowing for the simultaneous determination of omeprazole and diclofenac sodium in a pharmaceutical preparation. Identification and quantification of omeprazole in simple and combined (with diclofenac) pharmaceutical preparations was performed on silica gel 60F254 using one mobile phase: chloroform–methanol–ammonia (36:4:0.60, v/v). Diclofenac sodium was determined in the presence of omeprazole after 2D separation on silica gel using two mobile phases of the first phase of chloroform–methanol–ammonia (36:4:0.60, v/v) and the second mobile phase cyclohexane–chloroform–methanol–glacial acetic acid (6:3:0.5:0.5 v/v). The developed method is simple, economical, specific, precise, accurate, sensitive, and robust, with a good range of linearity for the quantification of omeprazole and diclofenac sodium. TLC in combination with densitometry can be used as an effective analytical tool for quality control and quantitative determination of omeprazole in simple and combined pharmaceutical preparations containing diclofenac sodium. TLC in combination with densitometry can be recommended for the analysis of omeprazole and diclofenac sodium in the absence of HPLC or spectrophotometer in the laboratory or to confirm results obtained with other analytical techniques.